2010
DOI: 10.1002/ajh.21879
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of minimal residual disease in acute myeloid leukemia with frequent and rare patient‐specific NPM1 mutations

Abstract: Nucleophosmin (NPM1) mutations in exon 12 are the most common genetic alternation in cytogenetically normal AML (CN-AML). Although mutation types A, B, and D represent the majority of cases, rare mutation variants of the NPM1 gene in individual patients do occur. In this study, we have evaluated a novel, DNAbased real-time quantitative polymerase chain reaction (RQ-PCR) for the detection of three of the most commonly occurring mutations and for six rare patient-specific mutation types, which represent 28% of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
31
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 15 publications
7
31
0
2
Order By: Relevance
“…The validation showed a reproducible sensitivity of the NPM1 RQ‐PCR ranging from 0.002% (2 × 10 −5 ) to 0.04% (4 × 10 −4 ) NPM1 type A mutant DNA, which is comparable to levels attained by others using a genomic DNA‐based RQ‐PCR approach for reproducible sensitivity (Gorello et al, ). The results also demonstrated that LOD 50 is near 0.001% (10 −5 ) of NPM1 type A mutant DNA, which also is comparable to levels attained by others (Chou et al, ; Dvorakova et al, ). Even the mere detection of a signal indicates the presence of leukemic cells, which may have a bearing on the risk of relapse (Chou et al, ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The validation showed a reproducible sensitivity of the NPM1 RQ‐PCR ranging from 0.002% (2 × 10 −5 ) to 0.04% (4 × 10 −4 ) NPM1 type A mutant DNA, which is comparable to levels attained by others using a genomic DNA‐based RQ‐PCR approach for reproducible sensitivity (Gorello et al, ). The results also demonstrated that LOD 50 is near 0.001% (10 −5 ) of NPM1 type A mutant DNA, which also is comparable to levels attained by others (Chou et al, ; Dvorakova et al, ). Even the mere detection of a signal indicates the presence of leukemic cells, which may have a bearing on the risk of relapse (Chou et al, ).…”
Section: Discussionsupporting
confidence: 88%
“…The key question about the use of these mutated genes as candidates for MRD monitoring regards their stability over the course of disease. NPM1 mutations can be identified in 45%–60% of patients with cytogenetically normal AML (Gorello et al, ; Chou et al, ; Dvorakova et al, ; Falini and Martelli, ; Kristensen et al, ; Buccisano et al, ), and is thus the most frequent genetic change. Many studies indicate that NPM1 mutations are stable at relapse, which makes it an ideal candidate for MRD assessment (Chou et al, ; Falini et al, ; Buccisano et al, ; Hubmann et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Вопрос о стабильности мутации NPM1 (сохра-нение клона) при рецидиве остается спорным [14,[37][38][39][40][41]. В нашем исследовании у 5 из 13 пациентов с рецидивами ОМЛ имелась мутация NPM1.…”
Section: клиническая онкогематологияunclassified
“…Значения в разных источниках варьируют от 3 до 5 log [14,30,33]. В настоящее время большинство исследователей рассматривают NPM1 как высокоспецифичный [34][35][36] и стабильный маркер оценки МОБ [14,[37][38][39][40][41]. Тем не менее в от-дельных наблюдениях отмечается утрата экспрессии мутации NPM1 при рецидивах ОМЛ, что ставит под сомнение ее использование для мониторинга эффек-тивности терапии.…”
Section: Introductionunclassified
“…Most of the NPM1m identified to date, as the type A mutation (75–80% of cases), are exon 12 frameshift mutations [1, 5, 8] leading to an aberrant accumulation of the protein in the cytoplasm [9]. Several protocols and methods have been developed for the detection of NPM1m including DNA sequencing of different mutation-specific RT-PCR assays [1013], denaturing high-performance liquid chromatography [14], capillary electrophoresis [15], locked nucleic acid-mediated polymerase chain reaction clamping [16], and high-resolution melting analysis [17]. Although these methods possess a high specificity to assess NPM1 mutational status at diagnosis, they always require direct sequencing for NPM1m characterization, a more expensive and time-consuming method.…”
Section: Introductionmentioning
confidence: 99%